Conductivity Mechanism of Ethyl-4-(7,7,8,8,9,9,10,10,10-nonafluorodecyloxy)Biphenyl-4′-Carboxylate (ENBC) - Canli, Nimet Yilmaz; Yildiz, Alptekin; Karanlik, Gurkan; Eran, Belkiz Bilgin; Okutan, Mustafa (AMER SCIENTIFIC PUBLISHERS, 2016)
In this study, ac conductivity and electronic properties of the Ethyl-4-(7,7,8,8,9,9,10,10,10-nonafluorodecyloxy)biphenyl-4'-carboxylate (ENBC) have been analyzed by means of dielectric and impedance spectroscopy measurements. The polarizing microscopy results show that ENBC exhibits enantiotropic Smectic A (SmA) mesophase. The real (epsilon') and imaginary (epsilon '') parts of dielectric constant have been calculated by capacitance method. The dielectric strengths have been calculated as 25.5 and 26.5 for 0 gauss and 5000 gauss, respectively. The applying magnetic field to ENBC increases the dielectric strength. DC behavior frequency interval of ENBC which evidenced by the AC conductivity results, has also been increased as a result of the application of magnetic field. It has been determined that the conductivity mechanism of the ENBC alters from CBH model to QMT behavior for 0 gauss. In the low frequency region DC conductivity mechanism has been observed with applying magnetic field. In the high frequency region, it has been determined that the conductivity mechanism approaches to QMT mechanism with or without magnetic field.
Keywords: Liquid Crystal; Ac Conductivity; Dielectric Strength; Impedance Spectroscopy; FREQUENCY-DEPENDENT CONDUCTIVITY; DIELECTRIC-RELAXATION; AC-CONDUCTIVITY; BEHAVIOR; Engineering; Science & Technology - Other Topics; Physics